GeoEPIC: Innovating a Solution to Implement Virtual Field Experiences for Education in the Time of COVID-19 and the Post-Pandemic Era - Gielstra, Dianna; Moorman, Lynn; Cerney, Dawna; Cerveny, Niccole; Gielstra, Johan (Journal of Higher Education Theory and Practice, 2021)
The spring of 2020 marked the start of many countries closing their borders to travel due to the COVID- 19 pandemic. These closures disrupted travel and learning opportunities for K- 16 education. International field trips and study abroad programs were some of the first canceled opportunities with domestic field trips becoming more complicated to implement safely. With termination of these experiences, students lost cooperative and collaborative opportunities for place-based, field-based education. To address these losses of situated learning opportunities for students, a digital learning platform was developed to increase access to educators and students to free virtual field-based experiences. The platform is enhanced to allow teachers easy adoption of resources with supporting workshops to help educators in creating and delivering this rich education content through authentic, virtual landscapes.